Successful treatment of placenta accreta spectrum disorder using management strategy of serial uterine artery embolization combined with standard weekly and a 8-day methotrexate/folinic acid regimens at 7 weeks of gestation - Min-Min Chou; Jia-Chun Yuan; Yaw-An Lu; Sheng-Wei Chuang (Elsevier, 2020)
Objective: We describe our experience with serial uterine artery embolization (UAE) combined with standard weekly methotrexate and a eight-day methotrexate/folinic acid (MTX/FA) treatment regimen in the management of placenta accreta spectrum (PAS) disorder at 7 weeks of gestation. Case report: A 38-year-old woman, gravida 2 para 0, with a history of myomectomy, was referred for ultrasound (US) evaluation due to suspected cervico-isthmic pregnancy. Transvaginal US image showed a viable embryo with a disproportionately bigger placenta encircling the fetus and completely covering the internal os of the cervix at 7 weeks of gestation. Color Doppler imaging revealed diffuse intraplacental and periplacental vascularity. Patient chose to terminate the pregnancy but attempted to preserve the uterus for future fertility following counseling. Serial UAE procedures were performed using Gelfoam and metallic microcoils. Two courses of a standard weekly MTX and a eight-day MTX/FA treatment regimen were administered to accelerate placental regression. The beta-hCG gradually decreased to a normal level, and an ultimate resolution of the PAS disorder was observed at 110 days after treatment. Conclusion: Early diagnosis of the PAS disorder could result in better obstetric outcome through earlier intervention using serial UAE combined with standard weekly and a eight day MTX//FA regimen in the first trimester of pregnancy.